DEMOCRATIZATION OF ACCESS TO MENTAL HEALTH IN A PSYCHOLOGY SCHOOL SERVICE (Citizenship in Action: Extension and Culture Magazine, 2025)
Education in Psychology, since its implementation as a profession in 1962, is based on current legislation, psychological sciences and professional ethics. The regulation of the profession, expressed by law No. 4119/1962, states that courses must organize school services and modalities of application to education and work in accordance with the parameters of the current law and regulations of the Federal Council of Psychology (CFP) . Extensionist practices, based on their interventionist and formative character, are an important resource for promoting mental health in the territorial scope, seeking the protagonism of communities and the development of skills of professional techniques for interventionist management in the community. In this context, the present study sought to analyze the contributions of extensionist and territorial practices in mental health promotion practices, based on the performance of a school-service extension program. The extensionist actions developed at the University of the State of Minas Gerais service-school, in a unit located in the Minas Gerais triangle region, were developed with the structuring of triage services, psychological duty, production of informative booklets to the internal and external community to the university and the standardization of the documents used for the operation of the school-service. In this way, the results and scope of the Psychosocial Care Service Extension Program (SAP), linked to the university's school service, are analyzed and discussed with the aim of offering referrals on the effects and contributions to the articulation and inseparability of the dimensions pillars of university education in the fields of teaching, research and extension. The study considered that extensionist practices, as the foundation of training, cannot be separated from the research and teaching interaction, guiding the action as an ethical, scientific practice and engaged with social transformation, whether in the scope of the population's access to citizenship and health mental health in the territory, or with the development and improvement of professional techniques engaged with clinical-political issues.
Keywords: extension practices; psychology; service-school